Examining changes in gramicidin current induced by endocannabinoids. - Sultan Mayar; Audrey Cyr-Athis; Nazzareno D'Avanzo (PLoS ONE)
Endocannabinoids are a diverse family of lipid molecules, which circulate in the human body, impacting the cardiovascular and the nervous systems. Endocannabinoids can influence pain perception, appetite, stress responses, mood, memory and learning. Regulation of these lipids present a promising therapeutic avenue for numerous neurological disorders. In addition to acting as agonists to cannabinoid receptors (CBRs), endocannabinoids can also modulate the function of various ion channels and receptors independently of CBRs. This modulation of function can arise from direct binding to the channel proteins, or via changes to the lipid properties such as membrane elasticity/stiffness, curvature, or hydrophobic thickness. Here, we assess the effects of endocannabinoids on membrane properties by examining changes in gramicidin (gA) currents in Xenopus oocytes. Endocannabinoids from both classes (Fatty acid ethanolamides (FAEs) and 2-monoacylglycerols (2-MGs)) are studied and current-voltage relationships are assessed. We see no correlation between changes in gA currents and physiochemical properties of FAE endocannabinoids; namely carbon tail length, degrees of unsaturation, position of first unsaturated bond, and lipophilicity. On the other hand, gA currents correlate with the position of the first unsaturated bond, and inversely correlate with the degree of unsaturation of 2-MGs. Correlation of gA currents with the lipophilicity of 2-MG endocannabinoids depended on whether tails were saturated or unsaturated. Employing gramicidin channels as molecular force probes can enable both predictive and quantitative studies on the impact of bilayer-mediated regulation on membrane protein function by endocannabinoids.